2012
DOI: 10.1111/j.1348-0421.2012.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral immunization with attenuated Salmonella vaccine expressing Escherichia coli O157:H7 intimin gamma triggers both systemic and mucosal humoral immunity in mice

Abstract: Human infections with EHEC such as O157:H7 have been a great concern for worldwide food-industry surveillance. This pathogen is commonly associated with bloody diarrhea that can evolve to the lifethreatening hemolytic uremic syndrome. Animals are the natural reservoir where this pathogen remains asymptomatically, in steps of ingestion and colonization of the bowel. The bacterium is shed in the feces, contaminating the surroundings, including water and food that are directed for human consumption. A major playe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…The RV144 clinical trial suggested that vaccine-elicited HIV-1 envelope (Env)-specific humoral immune responses may have contributed to the partial protection observed for vaccinees (2), but mucosal immune responses were not assessed in that trial. In contrast, previous studies have shown that immunization with peptide, DNA, protein, or attenuated bacterial or viral vector-based vaccines through parental or mucosal routes may elicit antigen-specific humoral immune responses at mucosal sites in mice, nonhuman primates, and humans (3)(4)(5)(6)(7). However, the characteristics, functionality, and epitope specificity of vaccine-elicited mucosal antibody responses have not been fully explored.…”
mentioning
confidence: 76%
“…The RV144 clinical trial suggested that vaccine-elicited HIV-1 envelope (Env)-specific humoral immune responses may have contributed to the partial protection observed for vaccinees (2), but mucosal immune responses were not assessed in that trial. In contrast, previous studies have shown that immunization with peptide, DNA, protein, or attenuated bacterial or viral vector-based vaccines through parental or mucosal routes may elicit antigen-specific humoral immune responses at mucosal sites in mice, nonhuman primates, and humans (3)(4)(5)(6)(7). However, the characteristics, functionality, and epitope specificity of vaccine-elicited mucosal antibody responses have not been fully explored.…”
mentioning
confidence: 76%
“…The attenuated bacteria expressing intimin were still detectable in Peyer's patches and spleen, while in feces CFUs decreased in number from day 2 to 10 and subsequently were constant. Animals immunized with the attenuated Salmonella had reduced EHEC O157:H7 shedding post-challenge and increased production of IgA and IgG (Oliveira et al, 2012 ).…”
Section: Development Of Vaccines Against Ehecmentioning
confidence: 99%
“…Orally inoculated Salmonella enterica serovar Typhimurium x3987 expresing intimin was able to colonize the mice Peyer's patches and spleen, producing specific serum IgG and fecal IgA antibodies and reducing EHEC shedding after challenge [78]. Lactobacillus lactis expressing EspA or EspB induced antigen-specific humoral IgG responses.…”
Section: Immunization With Subunit Vaccinesmentioning
confidence: 99%